Phylogenetic Study of Several Parasitic Plant Species Based on The atp-1 Gene Sequence - Pratama, Ardo Cahya; Karuniasari, Nadaa; Rahmadini, Agnia Fadillah; Ezra, Achmad; Hose, Victor Alvianoes Guterez; Turhadi, Turhadi; Suyanto, Eko; Fatchiyah, Fatchiyah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2024)
The distinction between parasitic and non-parasitic plants can be determined by analyzing the atp-1 gene, which plays a vital role in respiration and is known for its high mutation rate. This study analyzed the kinship of parasitic plant subclass species through the construction of a phylogenetic tree based on atp-1 gene sequences. The atp-1 gene sequences of parasitic and non-parasitic plants with a total of 29 species were obtained from NCBI. The sequences were then aligned with ClustalW and analyzed for mutation patterns. Sequences that have been aligned, phylogenetic trees were made with MEGA11 software with the Maximum Likelihood method and analyzed using the iTOL website. The sequences were analyzed for similarity and kinship with Matrix Coefficient and Haplotype Construction. The atp-1 gene proved that parasitic plants (hemiparasites) are furthermore related to non-parasitic plants compared to holoparasite parasitic plants. Besides that, the kinship of parasitic plants can be analyzed by several methods, namely matrix coefficient to measure similarity, DnaSP to analyzing haplotype, and haplotype network to find out detailed information on mutations that occur. Matrix coefficients can also be used to measure specific similarities between species. It was found that the same subclass had high similarities, for example the species Santalum album and Heisteria parvifolia with a genetic distance value of 0.00574. Meanwhile, different subclasses have low similarity, such as Cassytha filiformis and Ombrophytum with a genetic distance value of 0.07871. This study shows that the atp-1 gene is effective in analyzing the kinship between parasitic and non-parasitic plants. Hemiparasites are genetically closer to non-parasitic plants than holoparasites, with higher genetic similarity within the same subclass.